Nghiên cứu chế tạo màng sinh học hydroxyapatit (HA) bằng phương pháp sol-gel trong môi trường etanol - Liên, Đỗ Ngọc; Sinh, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
The ethanol - based sol-gel method was used for synthesis of nanocrystalline hydroxyapatite. The HA coating has been prepared on alumina ceramic substrate by dipping into ethanol sol-gel suspension of Ca(NO3).4H2O and (NH4)2 HPO4. To achieve better biocompatibility and excellent mechanical performance of prostheses, HA coating is often fabricated on surface of bone substitute implant.